Bondariella Hustache e Bondar, 1942 (Coleoptera: Curculionidea: Curculionidae: Baridinae): descrição da terminália feminina e uma espécie nova - ROCHA, Geraldo Alonso Góes (2022)
Bondariella Hustache & Bondar, 1942 (Coleoptera: Curculionoidea: Curculionidae: Baridinae) is registered exclusively in Brazil, in association with palm flowers of the genera Euterpe Mart and Syagrus Mart. From six species of the genus, two occur in the Amazon biome (in association with species of Euterpe), two in the Caatinga biome and two in the Atlantic Forest biome (in association with species of Syagrus). In this study, a new species of Bondariella was collected in the Amazon (Altamira, Pará), in flowers of Euterpe sp. The new species was described, illustrated and compared with holotype, paratypes and lectotypes of the other species. Bondariella sp. nov. can be diagnosed by male sternum VIII in shape of a comma, bearning three setae, median lobe with sclerotized endophalus bearing an evident sclerite, and by spermateca with truncated cornum apex. Also, the mouthparts of the new species were described and illustrated, representing the first study of these characters for Bondariella. In addition, the female terminalia of the six known species of the genus were described and illustrated. The identification key for species of the genus proposed by Valente & Cordeiro (2015) was modified to include the new species and the female terminal characters. Bondariella sp. nov. represents the third species of the genus recorded for the Amazon biome and also in association with Euterpe.